2004
DOI: 10.1577/t03-080.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Fish Species Traits from Small Streams to Large Rivers

Abstract: To examine the relations between fish community function and stream size, we classified 429 lotic freshwater fish species based on multiple categories within six species traits: (1) substrate preference, (2) geomorphic preference, (3) trophic ecology, (4) locomotion morphology, (5) reproductive strategy, and (6) stream size preference. Stream size categories included small streams, small, medium, and large rivers, and no size preference. The frequencies of each species trait category were determined for each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 16 publications
9
106
0
Order By: Relevance
“…Nevertheless, this mechanism of community assembly predicts species additions moving downstream, which is not supported by our correlative niche models that show tributary species declining in abundance with stream size. Second, predator density tends to increase with stream size (Goldstein and Meador 2004), but our results represent performance in the absence of predation. Predation can strongly and directly affect survival through consumption (Schlosser 1988).…”
Section: Complementary Distributions Of Congenersmentioning
confidence: 79%
“…Nevertheless, this mechanism of community assembly predicts species additions moving downstream, which is not supported by our correlative niche models that show tributary species declining in abundance with stream size. Second, predator density tends to increase with stream size (Goldstein and Meador 2004), but our results represent performance in the absence of predation. Predation can strongly and directly affect survival through consumption (Schlosser 1988).…”
Section: Complementary Distributions Of Congenersmentioning
confidence: 79%
“…For 704 example, some authors (e.g., Poff and Allan 1995;Goldstein and Meador 2004) utilized a combination of various species traits, such as trophic ecology, reproductive biology, substrate preference, geomorphic preference, locomotion, body morphology, and reproductive strategy, in their assessment of the relationship between functional organization and hydrological variability. Others (e.g., Hoeinghaus et al 2007) used a combination of trophic ecology and life history characteristics in their examination of scale dependency in structuring factors associated with functional and taxonomic organization of stream fish assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, habitat templates predict changes in reproductive traits with habitat stability, such as increasing parental care with decreased variability (Townsend and Hildrew 1994). Other studies examined functional organization in various contexts, including longitudinal zonation (Schlosser 1982), hydrological stability (Poff and Allan 1995), landscape variability (Angermeier and Winston 1999), intercontinental convergence (Lamouroux et al 2002), river size (Goldstein and Meador 2004), and scale-dependency of structuring factors (Hoeinghaus et al 2007). …”
mentioning
confidence: 99%
“…Casatti et al (2006), Braga and Andrade (2005) and Goldstein and Meador (2004) also reported an increase in the number of species per stream order. This relationship of species richness and stream order is considered to be a result of the species area relationship (Angermeier and Schlosser, 1989).…”
Section: Discussionmentioning
confidence: 82%